Pengaruh Kinerja Keuangan, Kebijakan Deviden, dan Struktur Modal Terhadap Nilai Perusahaan: Perusahaan yang Terindeks di LQ45 pada Bursa Efek Indonesia Pada Tahun 2018-2023 - Dhimas Ajie Santoso; Sri Sudarsi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the influence of financial performance, dividend policy and capital structure on the value of the company. The sample in this study is companies indexed on LQ45 on the Indonesia Stock Exchange in 2018-2023 non-banking. The data analysis technique used used multiple linear regression. The results of the research show that partially ROE, DPR, and DER have a positive and significant effect on the company's value. Simultaneously, ROE, DPR, and DER have a significant effect on the company's value.